TEACHING ENGLISH VOCABULARY BY USING GUESSING GAME TO THE FIFTH GRADE STUDENTS 117 PALEMBANG - Yuliani, Sri (Universitas Muhammadiyah Palembang, 2017)
The aim of this study was to find out whether it was effective or not to teach English vocabulary by using guessing game to the fifth grade students of Elementary school 117 Palembang. The population of this study was all the students of elementary school 117 Palembang in the academic year of 2016/2017 with the total number of students was 205. Meanwhile, the sample of the study was taken convenience sampling method. There were 40 students who were classified as the control group and 40 students who were classified as experimental group. The method of the study was quasi experimental method. In collecting the data, the researcher gave a test. In analyzing the data, the researcher used student’s individual score, conversion score range, and t-test. Based on findings, independent sample t-test indicated that value of t-obtained was 5.046 at significant level p>0.005 for two-tailed test t-table is 1.9908. It was concluded that Ho was rejected and Ha was accepted. It is clear that teaching English vocabulary by using guessing game was effective to the fifth grade students of Elementary school 117 Palembang.